2019
DOI: 10.12681/jhvms.19615
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Antiviral Drug Screening System for Anti-Bovine Viral Diarrhea Virus (BVDV) Therapies

Abstract: Bovine viral diarrhea virus (BVDV) is an economically important animal pathogen affecting cattle. Despite the use of vaccination, test and slaughter practices, BVD remains a serious problem of cattle breeding. This study was conducted in order to develop a cell line that expresses some of BVDV sub-replicons. BVDV-NADL NS3 and 5’UTR were cloned in pWPI-linker B lentiviral plasmid at the upstream of EGFP gene. Consequently, lentiviral vectors containing BVDV-NS3 and BVDV-5’UTR were produced by using the second-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…The HELICc and nucleotide binding site conserved domain was chosen. Mokhtari et al produced MDBK cells expressed BVDV-5 UTR and BVDV-NS3 using lentiviral vectors (19), used single and multiple siRNA molecules opposed to NS3 CSFV, and showed that viral isolates from different subtypes are inhibited by this method (20). In the present study, for permanent expression of the target genes, the transduction was performed by a lentiviral vector.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The HELICc and nucleotide binding site conserved domain was chosen. Mokhtari et al produced MDBK cells expressed BVDV-5 UTR and BVDV-NS3 using lentiviral vectors (19), used single and multiple siRNA molecules opposed to NS3 CSFV, and showed that viral isolates from different subtypes are inhibited by this method (20). In the present study, for permanent expression of the target genes, the transduction was performed by a lentiviral vector.…”
Section: Discussionmentioning
confidence: 81%
“…Attenuated live vaccines or recombinant subunits for BDV are not commercially available. Pestivirus contaminants of modified live virus vaccines may cause a serious disease following their inoculation in domestic ruminants (17).…”
Section: Discussionmentioning
confidence: 99%